Mechatronic system for the promotion of physical activity in people with motor limitations: first insights - Pereira, Leandro (2019)
© 2019, Springer International Publishing AG, part of Springer Nature. The increase in the elderly population takes along concerns to health professionals. A way of helping health professionals and the elderly may be through the development of systems that allow people to maintain their mobility regardless of age and health problems that may arise, such as: obesity, Parkinson’s, hypertension, arthritis, diabetes and even the passive symptoms of stroke. This article has two main objectives, the first is the study and analysis of the available devices that help people with mobility problems and the second is the proposal of a system that permits the accomplishment of physical activity and rehabilitation in a pleasant way.